An evaluation of palladium-based catalysts for the base-free borylation of alkenyl carboxylates. (13th October 2021) - Gaube, Gregory; Pipaon Fernandez, Nahiane; Leitch, David C.
Abstract : Palladium catalysis can achieve the base-free borylation of alkenyl carboxylates, enabling direct access to functionalized enones and heterocycles. Abstract : Synthesis of organoboron derivatives is a key application of catalytic cross-coupling, with the Pd-catalyzed Miyaura borylation among the most versatile methods available. We have evaluated several Pd-based systems for borylation of alkenyl acetates and pivalates, with the optimal system heavily dependant on the substrate structure.